Demand-side flexibility in distribution grids: Voluntary versus mandatory contracting. (February 2023) - Nouicer, Athir; Meeus, Leonardo; Delarue, Erik
Abstract: In this paper, we investigate two schemes for contracting demand-side flexibility by the Distribution System Operator (DSO) at the planning stage: a voluntary demand-side connection agreement where consumers offer their flexibility and a mandatory demand-side connection agreement where the DSO sets the flexibility levels. For both schemes, we develop a bilevel optimization model where the DSO, in the Upper Level, sets the flexibility price and network tariffs. Residential consumers react to those signals in the Lower Level. They can be prosumers that invest in solar PV and batteries or passive consumers. Two regulatory issues are investigated. First, which option to choose for regulators between mandatory and voluntary demand connection agreements. We find that mandatory demand-side connection agreements result in higher welfare gains compared to voluntary ones and a lower price for flexibility. However, such agreements may entail some implementation issues and different curtailment levels among consumers. This connects with the second investigated issue investigated on how to implement mandatory demand connection agreements from equity and feasibility perspectives. When introducing a pro-rata constrained mandatory scheme, curtailing consumers equally, we find that welfare levels are still higher than under the voluntary scheme but lower than in the unconstrained mandatory scheme. Highlights: Mandatory and Voluntary demand-side connection agreements realise important welfare gains. Mandatory contracting achieve higher welfare gains than the voluntary one. Mandatory demand-connection agreements may create equity or feasibility issues. Pro-rata mandatory contracting prevails as a good compromise among the analysed schemes.